Land use change to perennial energy crops in Northern Italy: Effects on soil organic carbon sequestration and distribution, soil enzyme activities and microbial communities. - Cattaneo, Francesca <1983> (Alma Mater Studiorum - Università di Bologna, 2014)
Studies on soil organic carbon (SOC) sequestration in perennial energy crops are available for North-Central Europe, while there is insufficient information for Southern Europe. This research was conducted in the Po Valley, a Mediterranean-temperate zone characterised by low SOC levels, due to intensive management. The aim was to assess the factors influencing SOC sequestration and its distribution through depth and within soil fractions, after a 9-year old conversion from two annual systems to Miscanthus (Miscanthus × giganteus) and giant reed (Arundo donax). The 13C natural abundance was used to evaluate the amount of SOC in annual and perennial species, and determine the percentage of carbon derived from perennial crops. SOC was significantly higher under perennial species, especially in the topsoil (0-0.15 m). After 9 years, the amount of C derived from Miscanthus was 18.7 Mg ha-1, mostly stored at 0-0.15 m, whereas the amount of C derived from giant reed was 34.7 Mg ha-1, evenly distributed through layers. Physical soil fractionation was combined with 13C abundance analysis. C derived from perennial crops was mainly found in macroaggregates. Under giant reed, more newly derived-carbon was stored in microaggregates and mineral fraction than under Miscanthus. A molecular approach based on denaturing gradient gel electrophoresis (DGGE) allowed to evaluate changes on microbial community, after the introduction of perennial crops. Functional aspects were investigated by determining relevant soil enzymes (β-glucosidase, urease, alkaline phosphatase). Perennial crops positively stimulated these enzymes, especially in the topsoil. DGGE profiles revealed that community richness was higher in perennial crops; Shannon index of diversity was influenced only by depth. In conclusion, Miscanthus and giant reed represent a sustainable choice for the recovery of soils exhausted by intensive management, also in Mediterranean conditions and this is relevant mainly because this geographical area is notoriously characterised by a rapid turnover of SOC.